Selective Cytotoxicity of Medical Cannabis (Cannabis sativa L.) Extracts Across the Whole Vegetation Cycle Under Various Hydroponic and Nutritional Treatments - Malík, Matěj; Doskočil, Ivo; Pavlík, Jan; Ulman, Miloš; Praus, Lukáš; Kouřimský, Pavel; Lampová, Barbora; Kuklina, Alexandra; Tlustoš, Pavel (Cannabis and cannabinoid research, 2024)
Introduction: The use of Cannabis sativa L. in health care requires stringent care for the optimal production of the bioactive compounds. However, plant phenotypes and the content of secondary metabolites, such as phytocannabinoids, are strongly influenced by external factors, such as nutrient availability. It has been shown that phytocannabinoids can exhibit selective cytotoxicity against various cancer cell lines while protecting healthy tissue from apoptosis. Research Aim: This study aimed to clarify the cytotoxic effect of cannabis extracts on colorectal cell lines by identifying the main active compounds and determining their abundance and activity across all developmental stages of medical cannabis plants cultivated under hydroponic conditions. Materials and Methods: Dimethyl sulfoxide extracts of medical cannabis plants bearing the genotype classified as chemotype I were analyzed by high-performance liquid chromatography, and their cytotoxic activity was determined by measuring cell viability by methylthiazolyldiphenyl-tetrazolium bromide assay on the human colon cancer cell lines, Caco-2 and HT-29, and the normal human epithelial cell line, CCD 841 CoN. Results: The most abundant phytocannabinoid in cannabis extracts was tetrahydrocannabinolic acid (THCA). Its maximum concentrations were reached from the 7th to the 13th plant vegetation week, depending on the nutritional cycle and treatment. Almost all extracts were cytotoxic to the human colorectal cancer (CRC) cell line HT-29 at lower concentrations than the other cell lines. The phytocannabinoids that most affected the cytotoxicity of individual extracts on HT-29 were cannabigerol, Δ9-tetrahydrocannabinol, cannabidiol, cannabigerolic acid, and THCA. The tested model showed almost 70% influence of these cannabinoids. However, THCA alone influenced the cytotoxicity of individual extracts by nearly 65%. Conclusions: Phytocannabinoid extracts from plants of the THCA-dominant chemotype interacted synergistically and showed selective cytotoxicity against the CRC cell line, HT-29. This positive extract response indicates possible therapeutic value.
Keywords: Hydroponics; Caco-2 buňky; marihuana pro léčebné účely; tetrahydrokanabinol; hydroponie; Medical Marijuana; Cannabis; lidé; Humans; Caco-2 Cells; Dronabinol